BUMDESA SEBAGAI MOTOR PENGGERAK EKONOMI DESA BERBASIS KEARIFAN LOKALDI KABUPATEN BADUNG - Cokorda Gde Bayu Putra (JUIMA : JURNAL ILMU MANAJEMEN, 2018)
Badan Usaha Milik Desa thereafter called BUMDesa is a social business institution that provides the needs of the village communities. The Badung Regency Government always tries to encourage the villages in Badung Regency to form a BUMDesa by issuing the legal product of the Badung Regency Regional Regulation Number 1 on 2015 concerning the Establishment and Management of Village-Owned Enterprises. The research method in this study used a qualitative research with a descriptive approach, with a research focus are (1) the importance of the establishment of a BUMDesa in Badung Regency, (2) business opportunities that can be worked on by BUMDesa in Badung Regency and (3 ) the principle of financial management of BUMDesa in accordance with the values ​​of Balinese local genius based on Hinduism. The result of this study is that the existence of a BUMDesa must be in accordance with the laws and regulations and the Badung Regency Regional Regulation which is then regulated by the Village Regulation. Business development carried must be adopt the village's potential and the design of the Badung Regency Spatial Plan. For existence and sustainability, BUMDesa must be implemented Balinese local genius based on Hinduism such Slokantara, Catur Purusha Artha, and Tri Hita Karana.